2013
DOI: 10.1177/0300985813488894
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Classification of the Feline “Complex” Mammary Tumors as Ductal and Intraductal Papillary Mammary Tumors

Abstract: When compared with the canine species, feline mammary tumors (FMTs) are much less heterogeneous, with a predominance of simple malignant neoplasm. Benign FMTs are rare, and it is unclear if complex and mixed tumors exist in the feline. In this study, we selected for immunohistochemical analyses 12 FMTs that had unusual histologic features. A group of 8 (2 benign and 6 malignant) FMTs showed a biphasic epithelial/myoepithelial population and a very regular cord-like distribution in a "Chinese lettering" pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 30 publications
6
28
0
Order By: Relevance
“…Also, a progressive loss of HRs expression from non-neoplastic to neoplastic samples as well as from benign to malignant tumors was evidenced in accordance with the literature [18,21,38]. In addition, the subgroup of less aggressive grade I “ductal-associated” carcinomas, defined as ductal and intraductal papillary tumors by morphology and IHC [31], had an increased frequency of ERa positivity when compared to all other carcinomas. Furthermore, ERa and PR expression was positively correlated with CK8_18, a marker of well-differentiated luminal cells, and negatively correlated with tumor grade as previously described [18,21], again indicating of a loss of HRs in less differentiated and more aggressive tumors.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Also, a progressive loss of HRs expression from non-neoplastic to neoplastic samples as well as from benign to malignant tumors was evidenced in accordance with the literature [18,21,38]. In addition, the subgroup of less aggressive grade I “ductal-associated” carcinomas, defined as ductal and intraductal papillary tumors by morphology and IHC [31], had an increased frequency of ERa positivity when compared to all other carcinomas. Furthermore, ERa and PR expression was positively correlated with CK8_18, a marker of well-differentiated luminal cells, and negatively correlated with tumor grade as previously described [18,21], again indicating of a loss of HRs in less differentiated and more aggressive tumors.…”
Section: Discussionsupporting
confidence: 83%
“…Morphological diagnoses were based on the WHO classification [15] and on the recent literature [16,31] that describes new mammary tumor subtypes that includes the new categories of comedocarcinoma, ductal adenoma/carcinoma, and intraductal papillary adenoma/carcinoma. The ductal and intraductal papillary (“ductal-associated”) tumors were confirmed by IHC as biphasic (see later).…”
Section: Methodsmentioning
confidence: 99%
“…ME cells of a normal rabbit mammary gland show the concurrent expression of pancytokeratin, vimentin, smooth muscle actin (SMA), p63, and calponin [3]. This is in agreement with the immunostaining of mammary gland ME cells in women [8,11], dogs [12,13,14,15], and cats [13,16].…”
Section: Introductionsupporting
confidence: 61%
“…In cats, the relative frequency of mammary carcinomas in situ can be estimated between 1.6 and 18.8% of mammary carcinomas included in published series (11, 1721). Two histological subtypes in particular, described by Zappulli et al feline ductal carcinoma, and feline intraductal papillary carcinoma (22), correspond to mammary carcinomas in situ (surrounded by a monolayer of myoepithelial cells). There have also been descriptions of infraclinical mammary ductal carcinomas in situ that were adjacent to an excised mammary tumor in cats; in the series described by Burrai et al 28/203 cats (14%) had an asymptomatic ductal carcinoma in situ identified at histological examination of the mammary tumor that motivated mastectomy (23).…”
Section: Introductionmentioning
confidence: 99%